Acute osteomyelitis in a neonate: a case report - Sónia Andrade Santos; Sandra Soares Cardoso; Joana Magalhães; Clara Diogo; Inês Balacó; Cristina Alves; Isabel Andrade (Portuguese Journal of Pediatrics)
Introduction: Acute osteomyelitis is rare in neonates and remains a diagnostic and therapeutic challenge. Case report: Female neonate, 25 days old, assessed after presenting with a limp right arm, irritability, and pain from that very day. Spontaneous movements of the right arm were absent, with no signs of inflammation or trauma, no markers of inflammation, and normal arm radiography. She was admitted for monitoring, maintaining pseudoparalysis. On the second day, she presented with fever, positive markers of inflammation and an ultrasound suggesting right humerus osteomyelitis. She was started on cefotaxime and vancomycin. MSSA was isolated in the blood culture. She was transferred to a tertiary hospital due to loss of venous access and hospitalized on flucloxacillin. She completed six weeks of intravenous antibiotics and was discharged after 43 days, having improved. Radiography showed signs of bone remodeling and she was discharged without sequelae, with an Orthopedics follow-up consultation in one year. Discussion: Early diagnosis and prompt treatment may prevent complications. The authors highlight the importance of diagnostic suspicion, even in neonates with no risk factors.